Modelling animal health as a production factor in dairy production - Bjelkelöv Telldahl, Cassandra (2019)
Farm animal diseases affect livestock production in several different ways. From an economic perspective, diseases are an undesirable contribution to the production process. Diseases thereby lower the producer's profit margins by reducing animal health and causing unnecessary suffering to the animals. For dairy production, mastitis is the most severe disease and causes both reduced animal health, increased costs, and reduced milk yield. Subclinical mastitis can be recognized by an increase in the somatic cell count (SCC), which is, therefore, often used as an indicator of udder health and milk quality.